Pengaruh Profesionalisme dan Pengembangan Karir Guru Terhadap Kinerja Guru Sekolah Dasar Gugus Pramuka Muara Sugihan - Heni Oktafiana; Syaiful Eddy; Suherman Suherman (CV. Ulil Albab Corp, 2026)
This study aims to determine and analyze: (1) the influence of teacher professionalism on teacher performance; (2) the influence of career development on teacher performance; and (3) the simultaneous influence of teacher professionalism and career development on teacher performance. This research is a quantitative study using a multiple correlation method. The study was conducted in the Pramuka Cluster elementary schools in Muara Sugihan District with 69 teacher respondents. Data collection techniques included questionnaires, observation, and documentation. Construct validity was used for the validity test, while reliability was tested using Cronbach’s Alpha. Prerequisite analysis tests consisted of normality, homogeneity, and linearity tests, and the data were analyzed using simple linear regression and multiple regression techniques. The results of the study indicate that teacher professionalism and career development have both partial and simultaneous influences on the performance of elementary school teachers in the Pramuka Cluster, Muara Sugihan District. The influence of teacher professionalism and career development on teacher performance is 50.5%, while the remaining 49.5% is influenced by other variables not examined in this study.